Moving Beyond the Negative: Contributions of Positive and Negative Affect on Quality of Life in Patients With Generalized Anxiety Disorder. Issue 11 (November 2020) - Das, Akanksha; Clerkin, Elise M.; Tolin, David F.; Assaf, Michal; Diefenbach, Gretchen J.
Abstract : Abstract: Individuals with generalized anxiety disorder (GAD) report poorer quality of life (QOL) than do nonanxious controls. Further, although positive affect (PA) and negative affect (NA) have been shown to predict QOL, no previous literature has tested this relationship in the context of individuals with GAD. In the present study, we evaluated the unique and interactive contributions of PA and NA on QOL within a sample of individuals diagnosed with GAD ( N = 50). Specifically, a hierarchical regression was conducted to evaluate the unique contributions of PA, NA, and their interaction on QOL, over and above symptoms of depression. PA and depression symptoms were both significant predictors of QOL, whereas neither the main effect for NA nor the PA × NA interaction was statistically significant. Results suggest that, for those with GAD, PA uniquely contributes to QOL. Strategies to upregulate PA may be a useful treatment target for increasing QOL in individuals with GAD.